Perspectives of Meat Eaters on the Consumption of Cultured Beef (in vitro Production) From the Eastern Cape of South Africa - Falowo, Bamidele Andrew; Hosu, Yiseyon Sunday; Idamokoro, Emrobowansan Monday (Frontiers in Sustainable Food Systems, 2022)
The creation and growing popularity of cultured meat has raised mixed reactions among consumers about its originality, acceptability, edibility, and nutritional quality across the world. The perception and reaction of consumers to novel meat are influenced by a variety of factors, such as geographical location, media coverage, educational status, culture, and religion. Therefore, this study was designed to examine the perceptions of consumers on the consumption of natural vs. cultured beef in the Eastern Cape Province, South Africa. A total of 255 respondents were interviewed using structured questionnaires, and the data were analyzed using descriptive statistics and X2 tests. Interviewees included representatives from University (educated), urban (literate), and rural (semi-literate) communities. The results revealed the majority (63%) of the respondents had not heard about the concept of cultured beef production, of which 27% of them were men and 36% were women. More than half (53%) of the respondents indicated their willingness to eat cultured beef if offered to them after explaining the concept and process of making cultured beef to them. Among all factors that were analyzed, the participant level of education was found to significantly influence their willingness to eat cultured beef when available commercially. It is therefore concluded that the majority of consumers in this study supported the concept of cultured meat as an alternative way to complement conventional meat production and would be willing to eat it when provided.